Colour interpolation using adaptive window for Bayer colour filter array. Issue 23 (1st November 2014) - Kim, Yonghoon; Kim, Kibaek; Jeon, Gwanggil; Jeong, Jechang
Abstract : Most demosaicking solutions focus on improving the accuracy of direction estimation for interpolation, and they achieve a highly precise gradient estimation performance. Direction estimation techniques achieve great improvement in objective image quality; however, in terms of subjective image quality there are remaining demosaicking problems to solve. An adaptive window algorithm to reduce demosaicking artefacts by exploiting the colour similarity of neighbouring pixels is introduced. Experimental results confirm that the proposed method produces the best colour peak signal‐to‐noise ratio and FSIM performance, and achieves great improvement in subjective image quality.